Penyuluhan tentang Stroke Non-Hemoragik dan Latihan Range of Motion (ROM) di RSUD dr. Soeselo Kabupaten Tegal - Ahmad Zakiudin; Tati Karyawati; Dewi Robiatul Azizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Non-hemorrhagic stroke is a neurological disorder caused by blockage of blood flow to the brain due to clots, plaque buildup, or other arterial obstructions. This condition is commonly associated with atherosclerosis, which causes thickening and narrowing of blood vessel walls and may lead to thrombosis. Stroke occurrence is influenced by various risk factors, including hypertension as the primary factor, as well as smoking, lack of physical activity, unhealthy diet, alcohol consumption, increased lipid levels, obesity, stress, and depression. This community service activity aims to increase family knowledge and skills regarding non-hemorrhagic stroke management and Range of Motion (ROM) exercises as an effort to maintain and improve muscle strength, optimize blood circulation, and prevent complications such as limb deformities. The activity was conducted through health education involving explanations about stroke, risk factors, prevention, and demonstrations of proper ROM exercise techniques. The implementation of this activity is expected to improve families’ understanding and ability to provide appropriate support for stroke patients, particularly in performing ROM exercises regularly and correctly. Increased knowledge and practical skills among families can contribute to improving the quality of care, supporting patient recovery, and reducing the risk of further disability caused by non-hemorrhagic stroke.